Screening Method for M-Proteins in Serum Using Nanobody Enrichment Coupled to MALDI-TOF Mass Spectrometry. (6th January 2020) - Kohlhagen, Mindy C; Barnidge, David R; Mills, John R; Stoner, Joshua; Gurtner, Kari M; Liptac, Andrea M; Lofgren, Denise I; Vanderboom, Patrick M; Dispenzieri, Angela; Katzmann, Jerry A; Willrich, Maria A V; Snyder, Melissa R; et al.
Abstract: BACKGROUND: Current recommendations for screening for monoclonal gammopathies include serum protein electrophoresis (PEL), imunofixation electrophoresis (IFE), and free light chain (FLC) ratios to identify or rule out an M-protein. The aim of this study was to examine the feasibility of an assay based on immunoenrichment and MALDI-TOF-MS (MASS-SCREEN) to qualitatively screen for M-proteins. METHODS: Serum from 556 patients previously screened for M-proteins by PEL and IFE were immunopurified using a κ/λ-specific nanobody bead mixture. Following purification, light chains (LC) were released from their heavy chains by reduction. MALDI-TOF analysis was performed and the mass-to-charge LC distributions were visually examined for the presence of an M-protein by both unblinded and blinded analysts. RESULTS: In unblinded analysis, MASS-SCREEN detected 100% of the PEL-positive samples with an analytical sensitivity and specificity of 96% and 81% using IFE positivity as the standard. In a blinded analysis using 6 different laboratory personnel, consensus was reached in 92% of the samples. Overall analytical sensitivity and specificity were reduced to 92% and 80%, respectively. FLC ratios were found to be abnormal in 28% of MASS-SCREEN–negative samples, suggesting FLC measurements need to be considered in screening. CONCLUSIONS: MASS-SCREEN could replace PEL in a panel that would include FLC measurements. Further studies and method development should be performed to validate the clinical sensitivity and specificity and to determine if this panel will suffice as a general screen for monoclonal proteins.